Ethnomedicinal and pharmacological potential of marine macroalgae for CNS disorders: An overview - Yende, Subhash R.; Kapgate, Radha; Sumit K. Arora,; Shah, Sapan K.; Moharir, Keshav S.; Mishra, Ankit (Journal of Medicinal Herbs and Ethnomedicine, 2022)
Marine macroalgae or seaweeds have created a favourable implication in the area of biomedical sciences, due to the present of potential bioactive substances. Extensive studies are reported on neuropharmacological effects of terrestrial plants and their constituents but there is inadequate information on the potential application of marine macroalgae for behavioural and neurological disorders. This review will emphasize on recent studies and/or updates on bioactive compounds or extracts from marine macroalgae and their potential toward CNS disorders.